THE STUDENTS’ PERCEPTION OF CANVA APPLICATION AS A TOOL IN LEARNING WRITING SKILL - Rena Eka; Musarokah, Siti; Priharyanti (English Language Teaching Methodology, 2023)
The use of technology in English language learning can bring tremendous effects because it provides students with enjoyable learning opportunities and facilitates the development of their English language skills. In this context, the study aimed to investigate students’ perceptions of using the Canva application as a tool for learning writing skills in the explanatory text, namely cause and effect in SMA Negeri 11 Semarang in the academic year 2022/2023. The study was conducted using qualitative research. The sample of the respondents was XI MIPA 6 with a total of 36 students. The sampling technique used purposive sampling. A survey technique was used to collect the data by distributing the proposed questionnaire to the respondents through Google Forms. A questionnaire was used as an instrument consisting of 3 indicators requiring 10 items to obtain data related to measure students’ viewpoints on the utilization of Canva in learning writing skills. This study revealed that the Canva application proved to be a valuable resource in assisting students in cultivating their writing skills and it is regarded as a user-friendly resource since it can be conveniently reached via smartphones and personal computers. The features of Canva empower learners to exhibit their creativity in writing by using a wide variety of templates. It concludes that students can improve the quality of their writing by using Canva as a technological medium in the 21st century. Canva is a fascinating and well-chosen application and can be viewed by students as a valuable and functional learning tool to boost their writing.